2011
DOI: 10.5812/kowsar.1735143x.751
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of HBV Vaccination in Various Stages of Chronic Kidney Disease: Is Earlier Better?

Abstract: BackgroundDespite improvement in hepatitis B infection prevention through national vaccination programs, implementation of compulsory and thorough blood donor screening, and reduction of transfusion numbers due to erythropoietin administration,hepatitis B remains a major concern in hemodialysis (HD) centers [1]. Compared to aresponse rate of over 90% in the normal population, only 50 to 60% of those with endstage renal disease (ESRD) achieve protective antibody levels following immunization against hepatitis B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…This was similar to DaRoza et al’s study [30]. The seroconversion rate in the Hashemi et al study was 78%, (lower than the results of our study) [28]. Edey et al [31] in a review article explained that the 3-dose schedule of HBV vaccine in immunocompetent individuals may lead to a 90–95% seroprotection rate; however, in patients with renal failure, the rates were lower.…”
Section: Discussionsupporting
confidence: 89%
“…This was similar to DaRoza et al’s study [30]. The seroconversion rate in the Hashemi et al study was 78%, (lower than the results of our study) [28]. Edey et al [31] in a review article explained that the 3-dose schedule of HBV vaccine in immunocompetent individuals may lead to a 90–95% seroprotection rate; however, in patients with renal failure, the rates were lower.…”
Section: Discussionsupporting
confidence: 89%
“…In the study by Hashemi et al (14) a higher estimated GFR was not associated with significantly improved seroconversion, but their data (not adjusted for significant differences in age, body mass, and hemoglobin between groups) also indicate statistically borderline decrease (P = 0.067) in positive response with deteriorating GFR: 80% in CKD stage 3, 76% in CKD stage 4 and 67% in CKD stage 5. Moreover, data by Hashemi et al (14) showed a significant positive correlation between an anti-HBs titer and estimated GFR.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, data by Hashemi et al (14) showed a significant positive correlation between an anti-HBs titer and estimated GFR. CKD stage, however, was not associated with seroconversion in the multivariate analysis.…”
Section: Resultsmentioning
confidence: 90%
“…Subjects in the studies among adults and children generally lacked comorbidities (including kidney disease) other than diabetes. One study among hemodialysis/chronic kidney disease patients included only subjects with chronic kidney disease (i.e., no hemodialysis patients) (32), and three studies included both hemodialysis and chronic kidney disease patients (36,42,44), one of which also included peritoneal dialysis patients (44). The remainder were comprised entirely of hemodialysis patients.…”
Section: Resultsmentioning
confidence: 99%